Stereotype Threat Affects Financial Decision Making - Carr, Priyanka B.; Steele, Claude M. (Psychological Science, 2010)
The research presented in this article provides the first evidence that one’s decision making can be influenced by concerns about stereotypes and the devaluation of one’s identity. Many studies document gender differences in decision making, and often attribute these differences to innate and stable factors, such as biological and hormonal differences. In three studies, we found that stereotype threat affected decision making and led to gender differences in loss-aversion and risk-aversion behaviors. In Study 1, women subjected to stereotype threat in academic and business settings were more loss averse than both men and women who were not facing the threat of being viewed in light of negative stereotypes. We found no gender differences in loss-aversion behavior in the absence of stereotype threat. In Studies 2a and 2b, we found the same pattern of effects for risk-aversion behavior that we had observed for loss-aversion behavior. In addition, in Study 2b, ego depletion mediated the effects of stereotype threat on women’s decision making. These results suggest that individuals’ decision making can be influenced by stereotype concerns.